Calculation model of spaciousness in rooms with windows-Experimental procedure for spaciousness evaluation using VR-. Issue 1 (1st November 2022) - Nishihara, S; Okada, M; Miyake, H; Yamaguchi, H; Yoshizawa, N
Abstract: Spaciousness is an important psychophysical value of space which has impacts on building occupants' satisfaction and wellness. Previous research revealed through subjective experiments in spaces without windows that spaciousness is affected not only by the physical volume of space but also by lighting environment, and the effect can be estimated with a calculation model with average luminance and "dark-part-reduced visible volume". The purpose of this study is to expand the scope of the calculation model to spaces with windows through subjective experiment, and for that, to improve the experimental procedure for steady comparison of various spaces in size avoiding stimulus range bias. We determined "typical standard conditions" as three sizes of simple rectangular spaces with uniform general lighting to cover experiments which use comparative condition spaces in visible volume of 10m 3 -2490m 3 . These are created with Virtual Reality to enable subjects to compare spaces apart from each other in reality, and to reduce the cost of preparing various spaces. We conducted a subjective experiment with this improved procedure in a room with windows and revealed that the accuracy of calculation model can be improved by additionally considering configuration factors of windows and applying different weighting factors to the volume corresponding to the windows.